Redesign the Competence Business Strategy of SMEâs in Dealing withASEAN Economic Community (AEC) Trade Liberalization 2015Case Studies: SMEâs Creative Industry Sector in Bandung - Teddy Fauzi (UBL, 2013)
The establishment of ASEAN Economic Community (AEC) aims to form a single market as an implementation of trade liberalization. The existence of the AEC will impact directly to SMEâs development in Indonesia in the future. There are approximately 8 million SMEâs in West Java which one of them is creative industry sector. It plays very important part in overall growth of economy for years.Over twenty yearâs period, between 1990-2010, creative industry sector of SMEâs in Bandung is more focused on domestic market but by establishment of AEC, absolutely necessary redesign their competence business strategy in order to be able to take advantage new AEC market.To develop this creative industry it is believed that SMEâs should solve their problems. There are 5 (five) major problems that are identified by the Department of Commerce for achievement in 2015. The five main issues are:(1) The quantity and quality of human resources; (2) Climate conducive to starting and running business; (3) Awards/appreciation for Indonesiaâs creative personality; (4) Accelerating the growth of information and communication technology; (5) Financing institution that supports the creative industryâ (Natawiria: 3).In general, export most of our products still faced various problems such as capital cost and logistic are still high.In conclusion, the existence of the AEC will creates new paradigm and global challenges so that our SMEâs products, including creative industry products created by SMEâs in Bandug will compete with other products produced by other AEC members. Therefore, redesign competence business strategy of SMEâs absolutely required.